Comparative Study Production of Exopolysaccharide (EPS) by Lactic Acid Bacteria (L. casei and L. plantarum) in Different Media (Dates and Mulberry juice) - Elok Zubaidah; Yusry Muqit Suryawira; Ella Saparianti (Agroindustrial Journal, 2017)
Exopolysaccharides (EPS) are polysaccharides that are secreted by some strains of bacteria. E PS contribute in health improvement where it has prebiotic properties, immunostimulatory, anti- tumoral, and hypocholesterolemic effects. A number of Lactic Acid Bacteria (LAB) has ability t o synthesise Exopolysaccharides (EPS). This study aimed to determine the ability LAB (L. casei and L. plantarum B2) to produce EPS in different media (dates and mulberry juice). L. casei sh owed higher EPS production (3413.33 mg/L) than L. plantarum (3316.67 mg / L) were grown in medium dates juices. Based on the type of media, EPS production in dates juice medium higher t han mulberry juice as medium, and there are differences production of EPS by both types of isol ates (L. casei and L. plantarum) in both media. The growth rate of LAB does not always show a positive correlation with EPS formation.